Teologiese aantekeninge by die Jubileum van "Ons Theologische Seminarium" op Stellenbosch - R. M. Britz (Acta Theologica)
With reference to the jubilee of the Theological Seminary of the Dutch Reformed Church in Stellenbosch in 1909, this contribution emphasises the theological diversity within the Dutch Reformed Church at the time. A careful assessment of the contemporary Dutch Reformed theological and ecclesiastical journals reveals theintroduction of the critical theological views of what Bebbington described as the “Liberal Evangelicals.” Younger ministers among the evangelical faction of the Cape Dutch Church played a significant role in this regard. In their academic work they accommodated the results of the historical criticism and reflected on the significance of the human character of Scripture. The article thus tells the story of the initiation of an important — and different — theological conviction that influenced the Dutch Reformed Church throughout the 20th century.